Proteomic investigation of the Alzheimer's risk gene MEF2C in microglial like cells. (December 2021) - Ballard, Cerys H; Blake, Derek J; Hill, Matt
Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder for which there are no disease‐modifying therapies. Genome‐wide association studies and next‐generation sequencing have identified over 50 susceptibility loci for AD (1). These include loci containing the transcription factor MEF2C, a master regulator of microglia development and function. In microglia, AD risk single nucleotide polymorphisms (SNPs) are enriched in open chromatin regions that contain DNA binding motifs for MEF2C (2). Disrupted DNA binding due to genetic variation at these sites or altered gene expression in cis may lead to impaired transcriptional control by MEF2C. This implicates the MEF2C transcriptional network as genetic risk mechanism of AD and investigation into the MEF2C interactome in microglia may provide functional and mechanistic insights into the molecular processes involved in AD pathogenesis. Method: To explore this, Co‐IP‐Mass Spectrometry of endogenous Mef2c has been used to identify its protein isoforms, post‐translational modifications, upstream regulators and interacting partners which may be integral to its biological function. Result: The first Co‐IP‐MS interactome of Mef2c in microglia‐like cells will be presented. Protein partners of this AD‐relevant transcription factor have been identified. These include a novel interactor Oasl1 which is involved in the innate immune response, the transcriptional repressors Hdac4 and Hdac5, and members of the Hira complex which appear to be holding Mef2c predominantly in a repressed state in basal BV2 cells. Conclusion: The identification of these partners allows for a better understanding of Mef2c regulation and function as a master regulator of microglia and AD risk. This has provided insights into the molecular processes involved in AD, and the pathways through which AD relevant biology is regulated. References: (1) Sims, R. et al. 2020. The multiplex model of the genetics of Alzheimer's disease. Nature Neuroscience 23, p. 311‐322. (2) Tansey, K. E. et al. 2018. Genetic risk for Alzheimer's disease is concentrated in specific macrophage and microglial transcriptional networks. Genome Medicine 10(14).